Germination Responses of Ryegrass (Annual vs. Perennial) Seed to the Interactive Effects of Temperature and Salt-Alkali Stress - Lin, Jixiang; Hua, Xiaoyu; Peng, Xiaoyuan; Dong, Bolin; Yan, Xiufeng (Frontiers in Plant Science, 2018)
Ryegrass is considered a useful grass species for forage production and turf purposes. Annual ryegrass (Lolium multiflorum Lam.) and perennial ryegrass (Lolium perenne L.) are two species of ryegrass with similar genomes. So far, little information exists concerning their physiological response to salt-alkali stress during germination stage, especially under different temperature regimes. Seeds of ryegrass were germinated at four alternating temperatures (10-20, 15-25, 20-30 and 25- 35°C) with salinity (NaCl) and alkalinity (Na2CO3, high pH) stresses. Results showed that optimal germination for both species under stress conditions occurred at higher temperatures (20-30°C for annual ryegrass; 20-30°C and 25-35°C for perennial ryegrass). Germination percentage and germination rate were both inhibited by increasing salinity or alkalinity, particularly higher alkalinities under any temperature. The inhibitory effects of the high salinity on germination were greater at 10-20°C for both species. However, seeds were subjected to more stress at 25-35°C under alkali stress even though the concentration was very low. In addition, both high and low temperatures lead to a markedly decrease in seed germination under alkali stress for perennial ryegrass. Recovery percentage of both species were highest at 400 mM salinity and 25 mM alkalinity under any temperature, especially 10-20°C, and 25-35°C also resulted in lower recovery percentages under both stresses for ryegrass. Moreover, annual ryegrass had a much higher recovery percentage than perennial ryegrass under such stress conditions. These results suggest that salinity stress and alkalinity stress are greatly different, and the salt-alkaline tolerance of ryegrass seeds is greatly affected by the interactions of temperature and salinity-alkalinity.